Synthesis of Chlorophosphoramidate Monomer Morpholinos and PMOs. Issue 2 (21st February 2023) - Kundu, Jayanta; Ghosh, Ujjwal; Ghosh, Atanu; Pattanayak, Sankha; Das, Arnab; Sinha, Surajit
Abstract: Phosphorodiamidate morpholino oligonucleotides (PMOs) are a successful class of antisense reagents that efficiently modulate gene expression. Because PMOs do not follow standard phosphoramidite chemistry, optimized synthetic protocols for these compounds are relatively scarce in the literature. This paper presents detailed protocols for synthesizing full‐length PMOs using chlorophosphoramidate chemistry by manual solid‐phase synthesis. We first describe the synthesis of Fmoc‐protected morpholino hydroxyl monomers, and the corresponding chlorophosphoramidate monomers, from commercially available protected ribonucleosides. The new Fmoc chemistry necessitates the use of a milder base, such as N ‐ethylmorpholine (NEM), and coupling reagent, such as 5‐(ethylthio)‐1 H ‐tetrazole (ETT), which are also tolerated for acid‐sensitive trityl chemistry. These chlorophosphoramidate monomers are then employed for PMO synthesis in a manual solid‐phase procedure using four sequential steps. The synthetic cycle for each nucleotide incorporation consists of (a) deblocking of the 3′‐ N protecting group using an acidic deblocking cocktail for trityl and base deblocking for Fmoc, (b) neutralization, (c) coupling in the presence of ETT and NEM, and (d) capping of the unreacted morpholine ring‐amine. The method uses safe, stable, and inexpensive reagents, and the process is expected to be scalable. After full‐length PMO synthesis and ammonia‐mediated cleavage from the solid support and deprotection, a range of PMOs with different lengths can be obtained conveniently and efficiently with reproducible good yields. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Synthesis of the novel Fmoc‐protected morpholino monomers Basic Protocol 2 : Synthesis of the phosphorylating reagent ( N, N‐ dimethylphosphoramic dichloride) required for chlorophosphoramidate monomer synthesis Basic Protocol 3 : Synthesis of chlorophosphoramidate monomers of Fmoc‐protected morpholino monomers Basic Protocol 4 : Solution‐phase standardization of dimer and trimer PMO synthesis using Fmoc chemistry Basic Protocol 5 : Solid‐phase synthesis, purification, and characterization of full‐length (25‐mer) no‐tail PMO using both trityl and Fmoc chemistry